The complete guide to plumbing : current with 2015-2018 plumbing codes (Cool Springs Press, an imprint of Quayside Publishing Group USA Inc., 2015)
From fixing a faucet to installing a drain line in a basement floor, this book has the answer to any home plumbing question. Packed with clear color photos and easy-to-understand descriptions, the basics of home plumbing systems are clearly explained, and all of the most popular plumbing projects are shown with beautiful step-by-step photos.